AIRE Gene Mutation Presenting at Age 2 Years With Autoimmune Retinopathy and Steroid-Responsive Acute Liver Failure: A Case Report and Literature Review - Sakaguchi, Hirotaka; Mizuochi, Tatsuki; Haruta, Masatoshi; Takase, Ryuta; Yoshida, Shigeo; Yamashita, Yushiro; Nishikomori, Ryuta (Frontiers in Immunology, 2021)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare monogenic autosomal recessive disorder caused by mutation in the autoimmune regulator (AIRE) gene. Patients usually are diagnosed at ages between 5 and 15 years when they show 3 or more manifestations, most typically mucocutaneous candidiasis, Addison's disease, and hypoparathyroidism. APECED-associated hepatitis (APAH) develops in only 10% to 40% of patients, with severity varying from subclinical chronic active hepatitis to potentially fatal acute liver failure (ALF). Ocular abnormalities are fairly common, most often keratopathy but sometimes retinopathy. Here we report a 2-year-old Japanese girl with an AIRE gene mutation who developed APAH with ALF, preceded by autoimmune retinopathy associated with anti-recoverin antibody before major symptoms suggested a diagnosis of APECED. Intravenous pulse methylprednisolone therapy followed by a corticosteroid combined with azathioprine treatment resolved ALF and achieved control of APAH. To our knowledge, our patient is the youngest reported to have ALF resulting from an AIRE gene mutation. Pulse methylprednisolone induction therapy followed by treatment with corticosteroid plus azathioprine may well be effective in other children with APAH and AIRE gene mutations.